2004
DOI: 10.1243/0309324042379301
|View full text |Cite
|
Sign up to set email alerts
|

Thickness and multi-axial stress creep rupture criteria of the Type IV component of a ferritic steel weld

Abstract: The paper summarizes previously derived constitutive parameters for temperatures of 575, 590, 600, 620 and 640 8C. Values of the multi-axial stress rupture parameter, #, are reviewed and recorded. This constitutive parameter set is used to determine the thickness of the Type IV material zone (0.7 mm). Values of Type IV multi-axial stress rupture parameter # are determined for a wide range of butt-welded pipe and cross-welded uni-axial specimens, and an interpolation equation is derived in terms of temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…Two different sets of constitutive parameters will be used for 590 • C: firstly, the set used by Hayhurst and Miller [12] which is summarised in Table 2; and, secondly, the set reported by Hayhurst et al [17] which is summarised in Table 3. The origins of the data used to calibrate the constitutive parameters, is now addressed.…”
Section: Selected Constitutive Data Setsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two different sets of constitutive parameters will be used for 590 • C: firstly, the set used by Hayhurst and Miller [12] which is summarised in Table 2; and, secondly, the set reported by Hayhurst et al [17] which is summarised in Table 3. The origins of the data used to calibrate the constitutive parameters, is now addressed.…”
Section: Selected Constitutive Data Setsmentioning
confidence: 99%
“…Multiaxial rupture parameter ν: Hayhurst et al [17] have concluded, following studies on a range of components over the temperature range 565-675 • C, that the constant value of ν = 2.8 provides acceptable predictions of observed behaviour.…”
Section: Data Used By Hayhurst Et Al [17] -mentioning
confidence: 99%
See 3 more Smart Citations